PENGARUH PENERAPAN TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR - Yayuk Subekti; Siti Halidjah; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to describe the effect of the application of make a match type on students' learning outcomes in thematic learning grade IV Of 42 Pontianak Kota Elementary School. This research is a quantitative descriptive study with the form of Quasi Experimental research. The population in this study was all grade IV students of Pontianak Kota State Elementary School which numbered 123 students and the population consisted of 28 students in the control class and 29 in the experimental students. The data collection technique used by measurement techniques and data collection tools used is a double-choice written test that amounts to 50 questions. The results showed that the average post-test study results of the experiment class were 81.50 and the average post-test control class was 75.53. Hypothetical test results using t-test obtained tcount2,141 and ttabSe1,985 for dk = 55 and 5 % Ha is accepted. From the results of the calculation of effect size (ES) obtained ES of 0.76 in the category of medium this results prove that there is an influence of the type of make a match on the learning results of students in thematic learning grade IV Elementary School 42 Pontianak Kota. Keywords: Influence, Make a Match Type,Learning Outcomes, Thematic